Incorporating sustainable practice in mechanics and structures of materials : proceedings of the 21st Australian Conference on the Mechanics of Structures and Materials, Melbourne, Australia, 7-10 December 2010 - Australasian Conference on the Mechanics of Structures and Materials (21st : 2010 : Melbourne, Vic.); Fragomeni, Sam (Boca Raton : CRC Press)
Includes bibliographical references and index